2019
DOI: 10.1038/s41598-019-38877-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of postharvest chilling injury in cherry tomato fruit reveals contrapuntal spatio-temporal responses to ripening and cold stress

Abstract: Postharvest chilling injury (PCI) reduces fruit quality and shelf-life in tomato ( Solanum lycopersicum L.). PCI has been traditionally studied in the pericarp, however its development is likely heterogeneous in different fruit tissues. To gain insight into PCI’s spatio-temporal development, we used postharvest biomarkers e.g. respiration and ethylene rates, ion leakage etc., to confirm the occurrence of PCI, and compared these data with molecular (gene expression), biophysical (MRI data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 93 publications
2
43
0
2
Order By: Relevance
“…These mutants also showed a modest reduction in CBF3 and CBF2 expression during cold exposure, suggesting the involvement of the three genes in Arabidopsis cold acclimation [ 51 ]. Similar to our results, CBF1 expression has been associated with chilling-resistant table grape cultivars induced by CO 2 -treatments that alleviated cold stress [ 40 , 41 ], revealing a diverse function of these genes depending on the fruit species, developmental stage, and severity of the cold stress [ 58 ]. In Hami melon fruit, an increase in CBF1 and CBF3 gene expression during cold storage was correlated with a lower CI index in the tolerant cultivar [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These mutants also showed a modest reduction in CBF3 and CBF2 expression during cold exposure, suggesting the involvement of the three genes in Arabidopsis cold acclimation [ 51 ]. Similar to our results, CBF1 expression has been associated with chilling-resistant table grape cultivars induced by CO 2 -treatments that alleviated cold stress [ 40 , 41 ], revealing a diverse function of these genes depending on the fruit species, developmental stage, and severity of the cold stress [ 58 ]. In Hami melon fruit, an increase in CBF1 and CBF3 gene expression during cold storage was correlated with a lower CI index in the tolerant cultivar [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…Different studies reported increased expression of CBFs in fruit, such as peach [ 28 , 55 ], mango [ 56 ], Hami melon [ 38 ], oil palm fruit [ 24 ], grape [ 40 , 41 ], and tomato [ 37 , 57 , 58 ] subjected to low temperature but also other stresses or ABA (abscisic acid) treatment, indicating a regulation by osmotic-related stress. Interestingly, in several instances, increases in their expression have been associated with a higher tolerance to chilling-related disorders [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of postharvest management is therefore to control this progression to senescence, i.e., to pause the ripening process for shipping and storage, and then to restart it with a minimal loss of quality. However, the processes that control the ripening-to-senescence transition dictate quality, creating a dilemma, whereby altering ripening biology via refrigeration, chemicals, or other means to lengthen shelf-life, often unavoidably disrupts ripening outcomes and reduces quality 28 . This leads to consumer rejection and postharvest waste.…”
Section: The Challenge Of the Postharvest Supply Webmentioning
confidence: 99%
“…Further, the symptoms are often hard to specifically ascribe to chilling injury: PCI-accelerated decay is often diagnosed as postharvest disease or premature senescence 212 , and poor flavor induced by PCI is often blamed on variety-type or early-harvest. PCI is insidious because it is difficult to detect, and it is therefore not properly documented 28 . It also adds constraints to postharvest management strategies for sensitive crops, as preventing PCI requires faster shipping at higher temperatures or shorter storage times.…”
Section: Complex Postharvest Traitsmentioning
confidence: 99%